Pengaruh Promosi dan Citra Merek terhadap Keputusan Pembelian pada Aplikasi Market Place - Susi Adiawaty; Albert Budiyanto Kambuno; Suryati Veronika; Salman Habeahan; Bernard E Silaban (JUDICIOUS, 2022)
The e-commerce and marketplace markets continue to grow rapidly in this digital era. In the midst of increasingly fierce competition, an effective marketing strategy is the key to maintaining existence and competitiveness. Promotion and branding are two important aspects of marketing strategy that play a key role in shaping consumer purchasing decisions. This research aims to analyze the influence of promotional activities and brand image on purchasing decisions of marketplace application users. Data is collected from consumers who make transactions via e-commerce applications in Indonesia. The multiple linear regression analysis method is used to test the relationship between promotional variables, brand image and purchasing decisions. The research results show that there is a significant positive influence between promotions and purchasing decisions of marketplace application users. However, brand image does not have a partially significant positive influence on purchasing decisions. However, simultaneously, promotions and branding have a significant influence on purchasing decisions in marketplace applications.